Peranan KH. Abdul Mu'thi dalam Pengembangan Dakwah Islamiyah Melalui Thariqat Qadiriyah Wanaqsabandiyah di Bengkalis - Arwan Arwan (An-Nida', 2013)
Tariqat Qadiriyya Naqshbandiyya, mosques and prayer rooms set up as a place of worship and a place of Propagation Method is done by KH. Abdul Mukti through Qadiriyya and Tariqat Naqshbandiyya, namely: (1) Da’wah bi al - hal and (2) bi Da’wah al - lisan. Da’wah bi al – hal somethings include: perfection mysticism, remembrance and manners to the murshid, foster a spirit of solidarity and mutual assistance